A Parabolic Transform and Averaging Methods for General Partial Differential Equations (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
Averaging method of the fractional general partial differential equations and a special case of these equations are studied, without any restrictions on the characteristic forms of the partial differential operators. We use the parabolic transform, existence and stability results can be obtained.